Pelatihan Penggunaan Aplikasi Kartu Pelajar Berbasis Desktop - Sulehu, Marwa; Latif, Nuraida; Mursalim, Mursalim; Awaliyah, Neneng; Taiboko, Dhea Monica (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2022)
The process of making student cards at SMA Mahaputra Tello Makassar is currently still using third party services in this case printing. In the process, the TU staff provides data to the printer and then waits for a month for the printing process. This is very ineffective because of the long build time. This Community Service aims to provide training for the staff of SMA Maha Putra Tello Makassar so that they can make desktop-based student cards. Later it helps facilitate staff in making student cards. The application of desktop-based student card making applications at SMA Maha Putra Tello Makassar is very much needed and can help the work of TU staff in making student cards and provide benefits to the school in this case reducing the cost of making student cards.